2014
DOI: 10.1016/j.foodqual.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dominance of Sensations of peanuts and peanut products in relation to Hutchings and Lillford’s “breakdown path”

Abstract: Hutchings and Lillford's (Journal of Texture Studies, 19, 103-115, 1988) proposed a "breakdown path" whereby particle size reduction occurs through mastication in conjunction with the secretion of saliva to form a swallowable bolus. The swallowing trajectory of whole peanuts, peanut meal and peanut paste were studied with the temporal dominance of sensations technique. The sensations for whole peanuts progressed from hard, to crunchy, to chewy, to soft and ended compacted on teeth.Predictably peanut meal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
(17 reference statements)
1
18
0
1
Order By: Relevance
“…The term “dominant” is defined as “the attribute that captures your attention, the most striking perception, but not necessarily the most intense sensation, at each moment of the evaluation” (Pineau et al, ). Numerous studies have used TDS to profile the dynamic perception of drinking (Dinnella, Masi, Naes, & Monteleone, ; Frost, Harbertson, & Heymann, ; Hutchings, Casanove, Schlich, & O'Riordan, ; Zorn, Alcaire, Vidal, Gimenez, & Ares, ) and chewing processes (Cheong et al, ; Lenfant, Loret, Pineau, Hartmann, & Martin, ; Mayhew, Schmidt, Schlich, & Lee, ; Rosenthal & Share, ). Rossella et al () reviewed the TDS method and concluded that it is more rapid than the time intensity (TI) method and is suitable for complex matrix profiling.…”
Section: Introductionmentioning
confidence: 99%
“…The term “dominant” is defined as “the attribute that captures your attention, the most striking perception, but not necessarily the most intense sensation, at each moment of the evaluation” (Pineau et al, ). Numerous studies have used TDS to profile the dynamic perception of drinking (Dinnella, Masi, Naes, & Monteleone, ; Frost, Harbertson, & Heymann, ; Hutchings, Casanove, Schlich, & O'Riordan, ; Zorn, Alcaire, Vidal, Gimenez, & Ares, ) and chewing processes (Cheong et al, ; Lenfant, Loret, Pineau, Hartmann, & Martin, ; Mayhew, Schmidt, Schlich, & Lee, ; Rosenthal & Share, ). Rossella et al () reviewed the TDS method and concluded that it is more rapid than the time intensity (TI) method and is suitable for complex matrix profiling.…”
Section: Introductionmentioning
confidence: 99%
“…TDS software (Morgenstern, The New Zealand Institute for Plant & Food Research Limited) was used to collect data in this study. The TDS procedure described by Rosenthal and Share () was followed. As assessors were untrained native English speakers, we did not create technical definitions of each attribute, but used terms with common meanings, being “compacted‐to‐teeth,” “granular,” “smooth,” “soft,” “sticky” and “thick.” Assessors were introduced to the software on an individual basis and the first of each triplicate sample presentation was used as a training exercise to familiarize the assessors with the products, the descriptive terms, the software and the testing protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of peanut butter, the melting point of the suspending medium is lower and depending on ambient temperature it can exist as an oily suspension, verging on solid paste, consisting of dry peanut solids suspended in peanut oil. When introduced to the mouth, the dominant sensations start as “chewy,” becoming “soft” and then finishing with “sticks to the palate” (Rosenthal and Share ). In terms of the HLM, one would expect that tahini (and depending on temperature peanut butter) starts with virtually no structure and with a high degree of lubrication due to the oil.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal dominance of sensations (TDS) showed the five sensations (hard → crunchy → chewy → soft → compacted on teeth) for whole peanut as time progressed, while only three sensations occurred for peanut meal (chewy → soft → compacted on teeth) and in the case of peanut paste only two sensations (soft → sticks to palate) existed. It is not surprising to notice that comminuted foods lose their “hardness” and “crunchiness” sensations, but Rosenthal and Share () considered it odd that in the case of peanut paste, “sticks to palate” increases with the time. These authors observed a similar behavior with other oils seed pastes (Hawthornthwaite, Ramjan, & Rosenthal, ) and they coined the phrase “hard to swallow.”…”
Section: Hutching and Lillford Model Of Food Oral Processingmentioning
confidence: 99%
“…and "crunchiness" sensations, but Rosenthal and Share (2014) considered it odd that in the case of peanut paste, "sticks to palate" increases with the time. These authors observed a similar behavior with other oils seed pastes (Hawthornthwaite, Ramjan, & Rosenthal, 2015) and they coined the phrase "hard to swallow.…”
Section: Structure Breakdownmentioning
confidence: 99%